Structuralism and Deconstruction in Biblical Scholarship: Annotated Bibliographies - Ernest Jnr Frimpong; Jonathan Edward Tetteh Kuwornu Adjaottor (Journal of Mother-Tongue Biblical Hermeneutics and Theology, 2024)
Academic referencing, though very significant in scholarship, has not been an easy task for both students and researchers, especially when one is restricted to following a particular referencing style either as instructed by one’s educational institution or by a publishing house through which one seeks a publication. In biblical scholarship, the philosophies of structuralism and deconstruction are very significant, especially as much as textual translation and interpretation are concerned. Several proponents have shared their scholarly views on how they individually appreciate these philosophical concepts. In an attempt to unravel some of such works without neglecting the authors and their central discussions, this paper employed a methodology through the construction of annotated bibliographies of such works. Findings indicated that while structuralism mainly studies the meaning of a text independently of its history and culture, deconstruction considers the world of the audience in line with the author’s intention and how that intention could be relevant to the new audience, taking into account the history of the text and the culture of the audience. Also, some of the key proponents of structuralism and its philosophical development include de Saussure, Levi-Strauss, Sasková and Titchener. Key proponents of deconstruction include Derrida, Norris, Ekem, Kuwornu-Adjaottor, Mugambi, and Nida. Significantly, with a maximum word count of 150 words and not less than 50 words, readers would understand key information contained in the sampled works of the authors through the annotations.